Short short story and image: The case of José María Merino (XXI Century. Spanish Literature and Culture, 2012)
The object of this study is describing the narrative mechanism of two bimedial short short stories by J.M. Merino which include a manipulated painting (“Nighthawks” vs “Las Meninas”). The study aims to explain why the manipulation provides, in one case, an imaginative reading (complementary story) and, in the other, an analytical-reflective one.
Keywords: Hybrid short short story; tableau vivant; manipulated painting; narrativation; José María Merino